Small aperture radial waveguide slot array antenna design and development for wireless local area network application - Choong, Lai Mun (2005)
The Radial Waveguide Slot Array (RWSA) Antenna is known for its good characteristics such as low profile, low cost, aesthetically pleasing, ease of installation and simple structure. This research project involves the design and development of the novel linearly polarized small aperture Radial Waveguide Slot Array (RWSA) Antenna for indoor WLAN applications operating based on ISM frequency band standard, with frequency range of 2.4 – 2.4835 GHz. Zeland Fidelity 4.0, a FDTD based antenna simulation is utilized to estimate the input impedance and radiation pattern of the antenna design. The second part of this project includes the antenna prototypes fabrication and experimental evaluation. Finally, the measurement analysis is compared with the theoretical result. The small aperture linearly polarized 2.4GHz RWSA antenna is successfully designed and developed for indoor Wireless Local Area Network access point. From the experimental evaluation, the RWSA antenna has validated its potential to be operated on the WLAN system